2019
DOI: 10.1101/851105
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Increased efficacy of histone methyltransferase G9a inhibitors against MYCN-amplified Neuroblastoma

Abstract: 11Targeted inhibition of proteins modulating epigenetic changes is an increasingly important priority in 12 cancer therapeutics, and many small molecule inhibitors are currently being developed. In the case of 13 neuroblastoma (NB), a paediatric solid tumour with a paucity of intragenic mutations, epigenetic 14 deregulation may be especially important. In this study we validate the histone methyltransferase 15 G9a/EHMT2 as being associated with indicators of poor prognosis in NB. Immunological analysis of 16G9… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…Transcriptome sequencing has demonstrated that neurotrophic receptor tyrosine kinase 1 may be a target of EZH2. Chen et al ( 31 ) reported that the MYCN gene binds to the EZH2 promoter, directly promoting EZH2 expression and EZH2 inhibition of neuronal differentiation in a PRC2-dependent manner ( 33 ). Tsubota et al ( 34 ) demonstrated that EZH2 inhibitors significantly repress the growth of tyrosine hydroxylase-MYCN NB mice, and that MYCN and PRC2 targets are positively correlated in NB.…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptome sequencing has demonstrated that neurotrophic receptor tyrosine kinase 1 may be a target of EZH2. Chen et al ( 31 ) reported that the MYCN gene binds to the EZH2 promoter, directly promoting EZH2 expression and EZH2 inhibition of neuronal differentiation in a PRC2-dependent manner ( 33 ). Tsubota et al ( 34 ) demonstrated that EZH2 inhibitors significantly repress the growth of tyrosine hydroxylase-MYCN NB mice, and that MYCN and PRC2 targets are positively correlated in NB.…”
Section: Discussionmentioning
confidence: 99%